The effects of topical diclofenac, flurbiprofen, and ketorolac on corneal sensitivity in normal cats - Roberts, Jordan Kay (Kansas State University, 2021)
Surface ocular diseases are common, vision threatening, and painful ophthalmic conditions encountered in cats. When possible, specific therapies for the treatment of an underlying cause are administered. However, clinicians are often compelled to use symptomatic treatments such as topical glucocorticoids to reduce ocular inflammation and nonsteroidal anti-inflammatory drugs (NSAIDs) to control clinical signs associated with ocular pain. Although topical NSAIDs are commonly used in the treatment of a variety of surface ocular diseases, studies demonstrating the effects of topically applied NSAIDs in cats are limited. This study served to investigate the immediate and prolonged dosing effects of three different topical NSAIDs on corneal sensitivity in healthy domestic shorthair cats. Twelve normal, non-brachycephalic domestic shorthair cats were enrolled in this prospective, randomized, masked, crossover study. To determine the immediate dosing effects, one drop of the assigned treatment (0.1% diclofenac sodium ophthalmic solution, 0.5% ketorolac tromethamine ophthalmic solution, or 0.03% flurbiprofen sodium ophthalmic solution) or control (0.9% saline) solution was applied to both eyes every five minutes for five applications, and corneal sensitivity was measured using a Cochet-Bonnet esthesiometer every 15 minutes for one hour. To determine the prolonged dosing effects, one drop of the treatment or control solution was applied to both eyes every 12 hours for five days, and corneal sensitivity was measured at the end of the last treatment. A 2-day washout period occurred between each group for both treatment phases. Neither topical 0.1% diclofenac sodium, 0.5% ketorolac tromethamine, nor 0.03% flurbiprofen sodium had any effect on corneal sensitivity immediately following repeated application or after prolonged twice-daily dosing in normal, non-brachycephalic cats.
Keywords: Corneal esthesiometer; Corneal sensitivity; Feline; Ophthalmic NSAID; Cochet-Bonnet